ANTERIOR CRUCIATE LIGAMENT AVULSION INJURIES IN MILITARY SOLDIERS: A TERTIARY CARE EXPERIENCE: Anterior Cruciate Ligament Avulsion Injuries - Chaudhary, Muhammad Nadeem; Hafeez, Sohail; Aslam, Memoona (Pakistan Armed Forces Medical Journal, 2018)
Objective: To evaluate the clinical outcome of fixation of anterior cruciate ligament avulsion injuries in Military Soldiers. Study Design: Descriptive case series. Place and Duration of Study: Orthopedic department, Combined Military Hospital (CMH) Rawalpindi, from Jun 2015 to Jun 2016. Material and Methods: Open reduction and screw fixation was done in 30 soldiers presenting with McKeever type III and IV avulsion fractures of anterior cruciate ligament. Outcome evaluation was carried out at 3 and 6 months. Lachman test was used for stability. Standard AP and Lateralx-rayswere taken to monitor bony healing. Lysholm score was used for functional evaluation. Results: All 30 patients showed complete healing at 3 months. Three patients revealed residual laxity. Mean extension loss was 5 degrees. Lysholm score improved from pre-operative mean of 29.97 (SD ± 5.46) to postoperative mean of 95.67 (SD ± 1.47). Conclusion: This study demonstrated operative fixation of Grade III and IV anterior cruciate ligament avulsion injuries as a successful surgical option in Military soldiers.